1998
DOI: 10.1191/096120398678920361
|View full text |Cite
|
Sign up to set email alerts
|

Prolactin levels in patients with systemic lupus erythematosus: a case controlled study

Abstract: Recent accumulated evidence suggests that prolactin (PRL) is an important immunomodulator and might have a role in the pathogenesis of systemic lupus erythematosus (SLE). Our aim was to assess the frequency of hyperprolactinemia in women with SLE and to evaluate its correlation with disease activity. PRL plasma levels were measured in 36 women with SLE and 20 age-matched healthy controls. We excluded patients with renal and/or hepatic failure, pregnant patients and patients taking drugs which could increase PR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(21 citation statements)
references
References 11 publications
1
19
0
1
Order By: Relevance
“…Estradiol stimulates prolactin secretion, and prolactin suppresses gonadal steroid synthesis (69,70). As shown in Table 4 and Figure 4, several studies have examined the relationship of prolactin and SLE in adults, comparing either the mean concentrations in patients with those of controls or normal and abnormal prolactin concentrations (hyperprolactinemia), with or without a control population (71)(72)(73)(74)(75)(76)(77)(78)(79)(80)(81)(82)(83)(84)(85)(86)(87). Seven of 10 female-only and 2 of 4 male-only SLE studies showed significantly increased serum prolactin concentrations in adult lupus patients compared with controls.…”
Section: Serum Prolactinmentioning
confidence: 99%
“…Estradiol stimulates prolactin secretion, and prolactin suppresses gonadal steroid synthesis (69,70). As shown in Table 4 and Figure 4, several studies have examined the relationship of prolactin and SLE in adults, comparing either the mean concentrations in patients with those of controls or normal and abnormal prolactin concentrations (hyperprolactinemia), with or without a control population (71)(72)(73)(74)(75)(76)(77)(78)(79)(80)(81)(82)(83)(84)(85)(86)(87). Seven of 10 female-only and 2 of 4 male-only SLE studies showed significantly increased serum prolactin concentrations in adult lupus patients compared with controls.…”
Section: Serum Prolactinmentioning
confidence: 99%
“…There is increasing evidence that prolactin functions also as an immunostimulatory molecule and, therefore, has the potential to contribute to the pathogenesis of autoimmune diseases (14)(15)(16)(17)(18)(19)(20)(21). An association between SLE and elevated prolactin levels has been suggested (22)(23)(24)(25)(26)(27)(28)(29); attempts to correlate prolactin levels with either global lupus activity (30)(31)(32)(33)(34)(35)(36) or specific organ involvement (37,38), however, have yielded varying results. Small-scale clinical trials in SLE with bromocriptine, a drug that blocks prolactin secretion by the anterior pituitary, have suggested a beneficial effect in patients with mild and moderate disease activity (25,39).…”
Section: Introductionmentioning
confidence: 99%
“…The peptide hormone prolactin belongs to the cytokine superfamily of the helix bundle peptide hormones (Goffin et al, 1996) and its receptors are genetically a part of the cytokine-hematopoietin receptor superfamily (Cosman, 1993). PRL is known to stimulate humoral and cell-mediated immune responses and may have a role in the pathogenesis of various autoimmune diseases, including systemic lupus erythematosus (Jimena et al, 1998;Neidhart, 1996). Furthermore, hyperprolactinemia was found in 46% of patients with primary Sjö gren's syndrome (Gutié rrez et al, 1994), correlation between high levels of prolactin and active disease has been observed (Allen et al, 1996), and serum PRL was recently associated with extraglandular disease manifestations in primary SS (Haga and Rygh, 1999).…”
mentioning
confidence: 99%